The Effect of Prenatal Yoga on Reducing Back Pain Intensity in Third Trimester Pregnant Women - Ningsih, Herwi Stiya; Yuliyanti, Linda; Fitri, Laila (Viva Medika, 2025)
Low back pain is caused by physiological changes during pregnancy, including maternal weight gain, spinal lordosis, decreased abdominal muscle strength, weight changes, and relaxation-mediated joint laxity. Pregnant women reported 16% of back pain during the first 12 weeks of pregnancy, 67% at 24 weeks, and 93% at 36 weeks. Management of back pain during pregnancy varies, one of which is doing prenatal yoga. This study aimed to determine the effect of applying prenatal yoga on reducing the intensity of back pain in third-trimester pregnant women. This type of research uses case studies. The population in this study was third-trimester pregnant women who experienced back pain with a sample of 3 third-trimester pregnant women. Data analysis in this research uses SOAP (Subjective, Objective, Analysis, and Management). The results of midwifery care show that back pain in pregnant women is reduced after doing prenatal yoga. This research concludes that there is an effect of applying prenatal yoga on reducing the intensity of back pain in pregnant women in the third trimester.